Isolation of two insecticidal toxins from venom of the Australian theraphosid spider Coremiocnemis tropix. (1st December 2016) - Ikonomopoulou, Maria P.; Smith, Jennifer J.; Herzig, Volker; Pineda, Sandy S.; Dziemborowicz, Sławomir; Er, Sing-Yan; Durek, Thomas; Gilchrist, John; Alewood, Paul F.; Nicholson, Graham M.; Bosmans, Frank; King, Glenn F.
Abstract: Sheep flystrike is caused by parasitic flies laying eggs on soiled wool or open wounds, after which the hatched maggots feed on the sheep flesh and often cause large lesions. It is a significant economic problem for the livestock industry as infestations are difficult to control due to ongoing cycles of larval development into flies followed by further egg laying. We therefore screened venom fractions from the Australian theraphosid spider Coremiocnemis tropix to identify toxins active against the sheep blowfly Lucilia cuprina, which is the primary cause of flystrike in Australia. This screen led to isolation of two insecticidal peptides, Ct1a and Ct1b, that are lethal to blowflies within 24 h of injection. The primary structure of these peptides was determined using a combination of Edman degradation and sequencing of a C. tropix venom-gland transcriptome. Ct1a and Ct1b contain 39 and 38 amino acid residues, respectively, including six cysteine residues that form three disulfide bonds. Recombinant production in bacteria ( Escherichia coli ) resulted in low yields of Ct1a whereas solid-phase peptide synthesis using native chemical ligation produced sufficient quantities of Ct1a for functional analyses. Synthetic Ct1a had no effect on voltage-gated sodium channels from the American cockroach Periplanata americana or the German cockroach Blattella germanica, but it was lethal to sheep blowflies with an LD50 of 1687 pmol/g. Highlights: Two peptides (Ct1a/Ct1b) lethal to sheep blowflies were isolated from venom of the Australian tarantula Coremiocnemis tropix . Ct1a/1b are initially produced as prepropeptide precursors that are post-translationally processed to the mature toxins. Ct1a/1b may have a novel fold as the cysteine pattern does not conform to the knottin motif commonly found in spider toxins. Ct1a does not target insect voltage-gated sodium channels.